The Relationship Between Knowledge And Attitudes Towards Ergonomic Behavior Of Employees At Upt Lik Magetan District - Reza Rifqi Izza, Ahmad; Widiarini, Retno; Ari Wibowo, Pipid (Jurnal Health Sains, 2024)
Ergonomic problems are related to the body's suitability to work tools when performing work tasks. Based on an initial study conducted by researchers on 10 employees at UPT LIK, Magetan Regency. There are 7 out of 10 workers who lack understanding about ergonomics such as how to lift weights, the maximum limit of the weight lifted, the use of Personal Protective Equipment (PPE), the effects of excessive weight lifting. Meanwhile, in the IKM section, understanding the principles of ergonomics is very important, because the work done by employees is closely related to ergonomics. The lack of awareness of workers in implementing ergonomic behavior is influenced by knowledge factors and work attitudes. Poor work knowledge and attitude are caused by the lack of ergonomics application by the industry to workers. In addition, workers also lack understanding of ergonomics in the work environment. This type of research is a quantitative research with cross sectional research. The population in this study is 230 respondents with a sample of 70 respondents in this study. The data of this study was obtained from the collection of questionnaire sheets and observation sheets. Data analysis using the Chi Square Test. The results of the bivariate test in this study showed that there was no relationship between the independent variable of knowledge and ergonomic behavior with p = 0.687 and there was a relationship between the independent variable of attitude and ergonomic behavior with p = 0.000 The conclusion in this study is that there is no significant relationship between knowledge and ergonomic behavior and there is a significant relationship between attitudes to ergonomic behavior. Keywords: Knowledge, Attitude, Ergonomic Behavior